2009
DOI: 10.1021/ef900651p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compression Ratio on Cycle-by-Cycle Variations in a Natural Gas Direct Injection Engine

Abstract: Cycle-by-cycle variations of a natural gas direct-injection spark ignition engine at different compression ratios were investigated. The results show that the lean burn limit of the natural-gas direct injection engine can be extended to a larger overall excess air ratio compared with that of the homogeneous charge natural gas engine. The coefficient of variations (CoV) of indicated mean effective pressure decreases with the increase of compression ratio. However, CoV of indicated mean effective pressure is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…Recently it also has been studied in homogeneous charge compression ignition (HCCI) engine processes [14], compression ignition engines [15] and also by using CFD simulations [16]. A traditional [17][18][19][20][21][22] estimator of the cycle-to-cycle variation is the Coefficient of Variation in Indicated Mean Pressure, COV IMEP . In this paper, the authors propose complementary considering the variation of the mass fraction burning rate of each individual cycle to characterize cyclic variation, as explained later (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it also has been studied in homogeneous charge compression ignition (HCCI) engine processes [14], compression ignition engines [15] and also by using CFD simulations [16]. A traditional [17][18][19][20][21][22] estimator of the cycle-to-cycle variation is the Coefficient of Variation in Indicated Mean Pressure, COV IMEP . In this paper, the authors propose complementary considering the variation of the mass fraction burning rate of each individual cycle to characterize cyclic variation, as explained later (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The situation is similar in HCCI engines where the CCV in IMEP also result mainly from variations in the initial stages of combustion. However, in direct-injection spark-ignition engines, it is found that CCV during the later combustion periods may also have strong influence on the cyclic pressure variations [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…In their recent work, Zheng et al [45,46] performed experimental studies of combustion in a natural gas direct-injection spark-ignition engine. In particular, they [46] analyzed the effect of compression ratio on the CCV of IMEP and investigated the interdependency between the CCV of IMEP and flame development duration, main combustion duration and total combustion duration.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that compression ratio was a key parameter for improving brake thermal efficiency when using hydrous ethanol as fuel [71]. Zheng et al [72] confirmed that CCV is lower with increased compression ratio, with the enhanced combustion characteristics. According to a study conducted by Young [73], there was 10% increase in power output for an identical fuel consumption and that a decrease in emissions from the engine could be achieved if the CCV could be reduced.…”
Section: Combustion Characteristics and Performance Of Hydrous Ethanomentioning
confidence: 99%